Kepatuhan Pelaksanaan Protokol Pencegahan Corona Virus Disease - 19 pada Tenaga Kesehatan di Ruang Poliklinik RST Wijayakusuma Purwokerto - Ratna Dwi Rahayu; Indri Heri Susanti; Amin Susanto (Universitas Harapan Bangsa, 2021)
One of the infectious diseases with the highest cases in recent months is coronavirus disease-19 (Covid-19). Health workers who treat COVID-19 patients are a group with a very high risk of exposure. As the COVID-19 pandemic grows, countries are increasingly stepping up IPC measures, including mandatory wearing of face masks and hand washing in all public places. The purpose of the study was to determine compliance with the implementation of the covid 19 prevention protocol in health workers in the Polyclinic Room of RST Wijayakusuma Purwokerto. Descriptive research design with cross sectional time approach. The sample in this study were 66 health workers in the Polyclinic Room of RST Wijayakusuma with a total sampling technique. The research instrument used an observation sheet with data analysis using a frequency distribution. The results of the study show that all respondents comply with the implementation of the Covid 19 prevention protocol (100%). Health workers who comply with the implementation of the Covid 19 prevention protocol, most of the respondents are 21-30 years old (56.1%), most of them are female (71.2%), have a professional/specialist education level (66.7%), and have years of service. > 5 years (56.1%)